Weather-resistant MS door and window adhesive and preparation method thereof
Through the combination of MS polymers and additives with specific ratios, weather-resistant MS door and window glue is prepared, which solves the problems of existing door and window glue aging and environmental pollution, and achieves low heat weight loss and high water-resistant UV and humidity-heat aging properties, which extends the The service life and reduces environmental pollution.
Patent Information
- Application Number
- CN202310115025.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-02-15
AI Technical Summary
Existing building doors and window glues are prone to aging after long-term use, resulting in water and air leakage problems. Some products reduce costs due to the addition of white oil, resulting in reduced service life and environmental pollution.
Weather-resistant MS doors and windows are prepared by combining MS polymers with specific ratios, benzophenone modified oligosilsesquioxane, calcium carbonate, polypropylene glycol, anti-aging additives, stabilizers and silane coupling agents. It can improve its water-ultraviolet and humidity-heat aging resistance, and ensure product performance through high-temperature dehydration and nitrogen protection processes.
It achieves low heat weight loss and volume non-shrinkage, significantly improving the water-resistant UV and humidity-heat aging performance of door and window adhesives, extending service life, and reducing environmental pollution.
Smart Images

Figure BDA0004078244020000021 
Figure BDA0004078244020000022 
Figure BDA0004078244020000023
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building adhesives, and in particular to a weather-resistant MS door and window adhesive and a preparation method thereof. Background Art
[0002] Building door and window adhesive is used to seal the joints between window frames and glass, and between window frames and internal and external walls. It plays a vital role in the air tightness, waterproofness, thermal insulation and sound insulation of doors and windows. Building door and window adhesive needs to withstand the weather such as wind, sun and rain all year round. The sealant is also constantly aging. Once the seal fails, it will cause water leakage, air leakage and other problems, which seriously affect the quality of the house and the user experience.
[0003] At present, silicone door and window adhesives are mainly used on the market. However, with price competition, the quality of products varies. Some inferior products add mineral oils such as white oil to replace silicone oil to reduce costs, which reduces the service life of door and window adhesives. In addition, the continuous evaporation of white oil causes pollution to doors, windows and the environment. Therefore, the development of a weather-resistant MS door and window adhesive has great use value and environmental significance. Summary of the invention
[0004] Based on this, it is necessary to provide a weather-resistant MS door and window adhesive and a preparation method thereof, which is not only suitable for the bonding, sealing and waterproofing of window frames and glass, and inner and outer walls, but also has lower thermal weight loss performance and better water-resistant UV and wet heat aging performance.
[0005] The present invention adopts the following technical solution:
[0006] The invention provides a weather-resistant MS door and window adhesive, which is mainly prepared from the following raw materials in parts by weight: 100 parts of MS polymer, 20-40 parts of benzophenone-modified oligomeric silsesquioxane, 200-400 parts of calcium carbonate, 80-120 parts of polypropylene glycol, 2-5 parts of anti-aging additive, 10-20 parts of stabilizer, 5-9 parts of silane coupling agent and 0.3-1 part of catalyst;
[0007] Wherein, the MS polymer is selected from a dimethoxymethylsilyl polyether polymer and a trimethoxy STP polymer in a weight ratio of (1-3):1.
[0008] The structural formula of dimethoxymethylsilyl polyether polymer is:
[0009]
[0010] The structural formula of trimethoxy STP polymer is:
[0011]
[0012] The structural formula of the benzophenone-modified oligomeric silsesquioxane is:
[0013]
[0014] Preferably, the MS polymer is selected from a dimethoxymethylsilyl polyether polymer and a trimethoxy STP polymer in a weight ratio of (1-2.5):1.
[0015] Preferably, the weather-resistant MS door and window adhesive is prepared from the following raw materials in parts by weight: 100 parts of MS polymer, 30 parts of benzophenone-modified oligomeric silsesquioxane, 280 parts of calcium carbonate, 90 parts of polypropylene glycol, 4 parts of anti-aging additive, 15 parts of stabilizer, 7 parts of silane coupling agent, and 0.6 parts of catalyst.
[0016] Preferably, the dimethoxymethylsilyl polyether polymer is selected from S810 resin, and has an average viscosity of 18-23 Pa·s at 25°C.
[0017] Preferably, the trimethoxy STP type polymer 3368T resin and 30000T resin have an average viscosity of 30-40 Pa·s at 25°C.
[0018] MS polymer uses the method of using the above two resins in combination, which can make the product have the advantages of fast deep curing and long operability; and in the preparation process, it is easy to coordinate high-temperature dehydration with calcium carbonate, polypropylene glycol, etc. to avoid the problem of the base material being too thick to be dehydrated.
[0019] Preferably, the calcium carbonate comprises nano calcium carbonate and heavy calcium carbonate in a weight ratio of (1-3):1, and the specific surface area of the nano calcium carbonate is 27±2m 2 / g of stearic acid modified calcium, and heavy calcium carbonate is 1250 mesh calcium powder.
[0020] Preferably, the stabilizer is selected from a mixture of bistrimethoxysilylethane and low alkalinity activated molecular sieve in a weight ratio of 1:(1-5). Chemical dehydration and physical adsorption dehydration are used together to achieve a better storage effect. The low alkalinity activated molecular sieve is preferably Luoyang Jianlong Micronano JLH-PU activated molecular sieve. The low alkalinity activated molecular sieve can not only assist in the thorough dehydration of bistrimethoxysilylethane and improve the storage stability of the product; and the low alkalinity characteristic has fewer side reactions than general molecular sieves; at the same time, small molecules decomposed by aging can be adsorbed to slow down aging and increase service life.
[0021] Preferably, the silane coupling agent is selected from a mixture of JH-AP1231 and JH-OP17 in a weight ratio of 1:1, so that fewer small molecules are released during the curing process of the MS glue, thereby improving the moisture and heat stability of the product.
[0022] Preferably, the anti-aging agent is selected from U-pack UV-7775. Liquid agents are more convenient to add and operate.
[0023] The present invention also provides a preparation method of weather-resistant MS door and window adhesive, comprising the following steps: adding dimethoxymethylsilyl polyether polymer, benzophenone-modified oligomeric silsesquioxane, calcium carbonate, polypropylene glycol, and an anti-aging additive into a dynamic mixer, stirring, vacuumizing, stirring, and heating to 110° C. for dehydration; after reducing the temperature in the dynamic mixer kettle to below 50° C., adding trimethoxy STP polymer, stabilizer, silane coupling agent, and catalyst step by step under nitrogen protection, mixing evenly under vacuum conditions, stopping the machine after the reaction is completed, filling with nitrogen to release the vacuum to normal pressure, and filling to obtain the product.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] The present invention introduces for the first time benzophenone-modified oligomeric silsesquioxane and a specific type and ratio of MS polymer, calcium carbonate, polypropylene glycol, auxiliary agent, stabilizer, silane coupling agent and catalyst compound in MS sealant, which synergistically improves the water-resistant UV performance and wet-heat aging performance of the product.
[0026] Compared with conventional silicone adhesive systems, the MS door and window adhesive of the present invention does not contain the alkane plasticizer of the silicone system, and instead uses polypropylene glycol, molecular sieves and other ingredients, so that the product has lower thermal weight loss and reduces the problem of volume shrinkage. DETAILED DESCRIPTION
[0027] The technical concept of the present invention is to provide a weather-resistant MS door and window adhesive and a preparation method thereof, which is prepared by screening specific types and proportions of MS polymers, benzophenone-modified oligomeric silsesquioxanes, calcium carbonate, plasticizers, additives, storage stabilizers, silane coupling agents and catalysts to achieve the technical effects of lower thermal weight loss and volume shrinkage performance and effectively improve water resistance, UV resistance and wet heat aging performance.
[0028] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly. The following embodiments are only used to illustrate the present invention, but are not only used to limit the scope of the present invention. Based on the specific embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention. In the embodiments of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the embodiments of the present invention, if not specifically specified, the technical means used are conventional means well known to those skilled in the art.
[0029] Some raw material sources:
[0030] Dimethoxymethylsilyl polyether type MS polymer was purchased from Kaneka Chemical S810 resin, with an average viscosity of 18-23 Pa·s at 25°C.
[0031] The trimethoxy STP type MS polymer was purchased from Ruiyang Litai 3368T resin and 30000T resin, and the average viscosity at 25°C was 30-40 Pa·s.
[0032] Polypropylene glycol was purchased from Shanghai Dongda Chemical Co., Ltd.
[0033] Stabilizer: low alkalinity activated molecular sieve, purchased from Luoyang Jianlong Micronano JLH-PU type.
[0034] Calcium carbonate: Nano calcium carbonate (stearic acid modified calcium with a specific surface area of 27±2 m2 / g) was purchased from Guangxi Huana New Materials Co., Ltd. Heavy calcium carbonate (1250 mesh) was purchased from Kelong Powder Co., Ltd.
[0035] The silane coupling agent is selected from Jianghan Chemical JH-AP1231 and JH-OP17; the anti-aging agent is selected from Lianlong U-packUV-7775.
[0036] Benzophenone modified oligomeric silsesquioxane, reference "J.wuhan Univ. Vol.61 No.1Feb.2015,067-072", the specific method steps are: add 16 parts of octachloropropyl cage silsesquioxane to a three-necked flask equipped with a thermometer and a reflux condenser to dissolve it in dry DMF, and then add 25 parts of 4-hydroxybenzophenone, 3 parts of sodium iodide and 17 parts of anhydrous potassium carbonate. Maintain the reaction at 100 ° C under argon protection for 8 hours and then stop, cool and centrifuge. Take the supernatant and distill under reduced pressure to remove DMF to obtain a yellow viscous substance that is dissolved in dichloromethane, washed with water 3 times to remove all remaining potassium and sodium salts, separate the organic layer, and drain the solvent to obtain benzophenone modified oligomeric silsesquioxane. Its internal skeleton is composed of an inorganic silicon oxygen core, and the outside is surrounded by 8 benzophenone groups.
[0037] Example 1
[0038] The present embodiment provides a weather-resistant MS door and window adhesive, which is prepared from the following raw materials in parts by weight: 100 parts of MS polymer (50 parts of S810 resin, 50 parts of 3368T resin), 30 parts of benzophenone-modified oligomeric silsesquioxane, 280 parts of calcium carbonate (180 parts of nano-calcium carbonate, 100 parts of heavy calcium carbonate), 90 parts of polypropylene glycol, 4 parts of UV-7775 additive, 15 parts of storage stabilizer (10 parts of activated molecular sieve, 5 parts of bistrimethoxysilylethane), 7 parts of silane coupling agent (3.5 parts of JH-AP1231, 3.5 parts of JH-OP17), and 0.6 parts of dibutyltin dilaurate.
[0039] The preparation method of the weather-resistant MS door and window adhesive of this embodiment comprises the following steps:
[0040] Weigh the raw materials according to the above ratio: add alkyl polyether MS polymer S810 resin, benzophenone modified oligomeric silsesquioxane, calcium carbonate, polypropylene glycol and additives into a dynamic mixer, stir for 0.5h, then evacuate and stir and heat to 110°C for dehydration for 2h; after reducing the temperature in the dynamic mixer to below 50°C, add STP polymer resin, storage stabilizer, silane coupling agent and catalyst step by step every half an hour under nitrogen protection, mix evenly under vacuum conditions, stop the machine and fill with nitrogen after the reaction is completed to release the vacuum to normal pressure, and quickly press the materials into a plastic packaging tube to obtain the finished product.
[0041] Example 2
[0042] The present embodiment provides a weather-resistant MS door and window adhesive, which is prepared from the following raw materials in parts by weight: 100 parts of MS polymer (65 parts of S810 resin, 35 parts of 3368T resin), 35 parts of benzophenone-modified oligomeric silsesquioxane, 350 parts of calcium carbonate (200 parts of nano calcium carbonate, 150 parts of heavy calcium carbonate), 90 parts of polypropylene glycol, 4 parts of UV-7775 additive, 15 parts of storage stabilizer (10 parts of activated molecular sieve, 5 parts of bistrimethoxysilylethane), 7 parts of silane coupling agent (3.5 parts of JH-AP1231, 3.5 parts of JH-OP17), and 0.7 parts of dibutyltin dilaurate.
[0043] The process steps of the method for preparing the weather-resistant MS door and window adhesive in this embodiment are the same as those in Example 1.
[0044] Example 3
[0045] The present embodiment provides a weather-resistant MS door and window adhesive, which is prepared from the following raw materials in parts by weight: 100 parts of MS polymer (60 parts of S810 resin, 40 parts of 30000T resin), 39 parts of benzophenone-modified oligomeric silsesquioxane, 220 parts of calcium carbonate (110 parts of nano-calcium carbonate, 110 parts of heavy calcium carbonate), 90 parts of polypropylene glycol, 4 parts of UV-7775 additive, 19 parts of storage stabilizer (14 parts of activated molecular sieve, 5 parts of bistrimethoxysilylethane), 7 parts of silane coupling agent (3.5 parts of JH-AP1231, 3.5 parts of JH-OP17), and 0.8 parts of dibutyltin dilaurate.
[0046] The process steps of the method for preparing the weather-resistant MS door and window adhesive in this embodiment are the same as those in Example 1.
[0047] Example 4
[0048] The present embodiment provides a weather-resistant MS door and window adhesive, which is prepared from the following raw materials in parts by weight: 100 parts of MS polymer (65 parts of S810 resin, 35 parts of 30000T resin), 22 parts of benzophenone-modified oligomeric silsesquioxane, 380 parts of calcium carbonate (270 parts of nano-calcium carbonate, 110 parts of heavy calcium carbonate), 80 parts of polypropylene glycol, 4 parts of UV-7775 additive, 12 parts of storage stabilizer (14 parts of activated molecular sieve, 2 parts of bistrimethoxysilylethane), 5 parts of silane coupling agent (2.5 parts of JH-AP1231, 2.5 parts of JH-OP17), and 0.7 parts of dibutyltin dilaurate.
[0049] The process steps of the method for preparing the weather-resistant MS door and window adhesive in this embodiment are the same as those in Example 1.
[0050] Comparative Example 1
[0051] This comparative example provides a MS sealant, the composition of which is substantially the same as that of the weather-resistant MS door and window sealant of Example 1, except that MQ silicone resin with a molar mass of 2000 g / mol is used instead of benzophenone-modified oligomeric silsesquioxane. The process steps of the preparation method of the MS sealant are the same as those of Example 1.
[0052] Comparative Example 2
[0053] This comparative example provides a MS sealant, the composition of which is substantially the same as that of a weather-resistant MS door and window sealant in Example 1, except that aminopropyl trimethoxysilane is used in equal amounts to replace JH-AP1231, and glycidyloxypropyl trimethoxysilane is used in equal amounts to replace JH-OP17. The process steps of the preparation method of the MS sealant are the same as those in Example 1.
[0054] Comparative Example 3
[0055] This comparative example provides a MS sealant, the composition of which is substantially the same as that of the weather-resistant MS door and window sealant of Example 1, except that the weight ratio of the S810 resin to the 3368T resin is 4:1.
[0056] Comparative Example 4
[0057] This comparative example provides a MS sealant, the composition of which is substantially the same as that of the weather-resistant MS door and window sealant of Example 4, except that the weight ratio of the S810 resin to the 30000T resin is 1:4.
[0058] Performance Testing
[0059] The MS sealants prepared in the above test examples were tested for performance, and the test items and test method steps are as follows:
[0060] (1) The test items were tested in accordance with GB / T 14683-20HM method. The substrates were 50*50mm anodized aluminum and glass, with a bonding area of 50*12*12mm. The test was performed after 21 days of room temperature curing.
[0061] (2) Room temperature tensile strength, tensile strength after water UV treatment, and tensile strength after double 85: According to the GB16776 test method, water UV aging for 300 hours, double 85 aging for 500 hours, after expiration, take out and place at room temperature for 2 hours before testing the tensile strength.
[0062] The test results are shown in the following table:
[0063] MS sealant performance test results statistics table
[0064]
[0065]
[0066] It can be seen from Table 1 above that, compared with Comparative Example 1, the water UV tensile strength and double 85 tensile strength of the MS door and window glue prepared in Examples 1 to 4 are both above 0.7MPa, the strength retention rate after aging is all above 75%, and the elastic recovery rate also has certain advantages; compared with Comparative Example 2, the thermal weight loss of the MS sealant products prepared in Examples 1 to 4 is less than 1.5%, showing good environmental protection and volume retention rate. Therefore, the glue products of Examples 1 to 4 fully meet the standard requirements of GB / T 14683 in the construction industry, have the advantages of low thermal weight loss and excellent operation time, and can effectively improve the water UV resistance and wet heat aging performance.
[0067] In addition, a large number of studies have found that:
[0068] Benzophenone-modified oligomeric silsesquioxane can be highly integrated with terminal alkyl MS polymer. When sunlight irradiates MS door and window adhesive and causes aging reaction, this inorganic-organic hybrid compound can play a good role in nano-size effect, blocking or decomposing and consuming radiation energy, protecting the MS polymer system from aging, thereby improving the anti-oxidation and moisture-heat stability of door and window adhesive.
[0069] Furthermore, the benzophenone-modified oligomeric silsesquioxane and the terminal alkyl MS polymer are compounded with calcium carbonate, polypropylene glycol, additives, stabilizers, silane coupling agents and catalysts in specific proportions, which can ensure that the overall operating time is appropriate, the thermal weight loss is low, the volume shrinkage is not large, and the weather resistance (water resistance, UV resistance and wet heat aging resistance) and other comprehensive properties are better.
[0070] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A weather-resistant MS door and window adhesive, characterized in that: It is mainly prepared from the following raw materials in parts by weight: 100 parts of MS polymer, 20-40 parts of benzophenone-modified oligomeric silsesquioxane, 200-400 parts of calcium carbonate, 80-120 parts of polypropylene glycol, 2-5 parts of anti-aging additive, 10-20 parts of stabilizer, 5-9 parts of silane coupling agent and 0.3-1 part of catalyst; Wherein, the MS polymer is selected from a dimethoxymethylsilyl polyether polymer and a trimethoxy STP polymer in a weight ratio of (1-3):1; The dimethoxymethylsilyl polyether polymer is selected from S810 resin, and the average viscosity at 25° C. is 18-23 Pa·s; The trimethoxy STP type polymer 3368T resin and 30000T resin have an average viscosity of 30-40 Pa·s at 25°C; The stabilizer is selected from a mixture of bistrimethoxysilylethane and low alkalinity activated molecular sieve in a weight ratio of 1:(1-5); The silane coupling agent is selected from a mixture of JH-AP1231 and JH-OP17 in a weight ratio of 1:1; The anti-aging aid is selected from UpackUV-7775.
2. The weather-resistant MS door and window adhesive according to claim 1, characterized in that: The MS polymer is selected from a dimethoxymethylsilyl polyether polymer and a trimethoxy STP polymer in a weight ratio of (1-2.5):
1.
3. The weather-resistant MS door and window adhesive according to claim 1 or 2, characterized in that: The calcium carbonate comprises nano calcium carbonate and heavy calcium carbonate in a weight ratio of (1-3):1, and the specific surface area of the nano calcium carbonate is 27±2m 2 / g of stearic acid modified calcium, and heavy calcium carbonate is 1250 mesh calcium powder.
4. A method for preparing the weather-resistant MS door and window adhesive according to any one of claims 1 to 3, characterized in that: The steps include: Add dimethoxymethylsilyl polyether polymer, benzophenone modified oligomeric silsesquioxane, calcium carbonate, polypropylene glycol and anti-aging additive into a dynamic mixer, stir, evacuate and stir, and heat to 110°C for dehydration; after reducing the temperature in the dynamic mixer to below 50°C, add trimethoxy STP polymer, stabilizer, silane coupling agent and catalyst step by step under nitrogen protection, mix evenly under vacuum, stop the machine and fill with nitrogen after the reaction is completed to release the vacuum to normal pressure, and fill to obtain the product.
Citation Information
Patent Citations
Environmentally friendly silane modified polyether sealant for home decoration and preparation method of environmentally friendly silane modified polyether sealant
CN109456725A
Single-component silane modified polyether sealant used in automobile glass rapid assembling, and preparation method thereof
CN110105907A
Environment-friendly high-displacement silicone sealant and preparation method thereof
CN114214024A
Single-component thermocuring sealant as well as preparation method and thermocuring method thereof
CN114369440A
Photoconductor with protective overcoat
US20060228638A1